On numerical doubly periodic wave solutions of the coupled Drinfel'd-Sokolov-Wilson equation by the decomposition method - İnç, Mustafa (Elsevier Science Inc, 2006)
In this paper, we consider obtaining approximate doubly periodic wave solutions of the coupled Drinfel'd-Sokolov-Wilson equation by using the Adomian decomposition method (ADM). Then we obtain the numerical Jacobi elliptic function solution for the initial conditions. The numerical results are compared with the known exact doubly periodic solutions. Most of the symbolic and numerical computations have been performed using the Computer Algebra System-Mathematica. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Adomian decomposition method; Adomian polynomials; coupled Drinfel'd-Sokolov-Wilson equation